Síndrome de Burnout y la personalidad en los docentes de la Unidad Educativa Isabél de Godín, Periodo 2017 - 2018” - Villa Tuquinga, Cristhian Santiago (2018)
This research project was developed with the purpose of analyzing the Burnout Syndrome and the Personality in the Teachers of the Isabel de Godín Educational Unit, and to establish the relationship between both variables to determine what personality trait could trigger this syndrome. The study had a non-experimental transversal design, where the results of the research will be indicated in a descriptive and quantitative manner. The population was constituted by 146 teachers, of which 26 teachers were the sample, based on the exclusion criteria, and through the application of the Maslach test, the number of teachers who would participate in the research was determined, so that Burnout syndrome was indentified, running in the period October 2017 - February 2018. It was possible to identify through the application of the Maslach Bournout Inventory (MBI) 1986 test, the prevalence of the syndrome in 71.4% of the women and 80.0% in the men, considering both sexes in an average the syndrome, and in the 16PF Personality Questionnaire 1993, emotional instability was identified as the first dominant trait with 100% in men and 38.1% in women, then it appears as the second dominant trait to carefree in 60.0% in men and in the case of women it is presented as the second dominant feature to the uninhibited and carefree in the same percentage of 28.6%. We worked with the statistical program SPSS version 23 and with the correlation test of Kendall's Tau_b, since we looked for the relationship between the two variables, however, a not significant relationship between both factors was found. With the aforementioned, it can be concluded that the features of emotional instability and unconcerned, would not be assessed as factors in the occasion of facing this condition that is usually found in teachers.